The legal basis of political representation: revisiting Orlando in the XXI century (TEST Antologia di Diritto Pubblico, 2025)
The contribution, starting from Vittorio Emanuele Orlando’s essay on the legal foundation of political representation, critically retraces the author’s thought. It highlights, in particular, how the aristocratic conception of representation presented in Orlando’s work is not compatible with the 1948 Italian Constitution and, indeed, is clearly rejected by it.
Keywords: Vittorio Emanuele Orlando; Political representation; Intermediate bodies; Political parties; Elections